STRATEGI PENGEMBANGAN USAHA BUAH NAGA DALAM UPAYA MENINGKATKAN PENDAPATAN MASYARAKAT DI NAGARI KACANG, KECAMATAN X KOTO SINGKARAK, KABUPATEN SOLOK - Meidiana Salsabila Putri; Khadijah Nurani (CV. Adiba Aisha Amira, 2024)
The background of this research is because there is still a lack of optimization of natural resources and human resources owned in developing dragon fruit businesses in Nagari Kacang, District X Koto Singkarak, Solok Regency. The dragon fruit business is a new sector developed by the people in Nagari Kacang by utilizing the land in their yards as land for growing dragon fruit plants. In addition, the market opportunity for dragon fruit yields is also very large so that it becomes an attraction for farmers who initially only manage seasonal crops and then switch to growing dragon fruit plants. However, over time, dragon fruit plants began to be attacked by pests and diseases which resulted in defects in the stems of the plants, which also affected the yields of the dragon fruit itself. So far, no farmers have been able to completely eradicate these pests and diseases. Therefore, it is necessary to conduct research related to how the dragon fruit business development strategy and its impact on increasing people's income. Then came the formulation of the problem, namely how to develop a dragon fruit business strategy in an effort to increase people's income in Nagari Kacang, X Koto Singkarak District, Solok Regency. This type of research with a qualitative descriptive approach using observation and interview data collection techniques. The results of the study stated that there are several strategies that can be applied by dragon fruit farmers in the development effort, namely utilizing the resources they have so that they can continue to expand the development of the dragon fruit business to increase people's income.